Raising awareness of the impacts of alcoholism on the performance of the Amazonas military police (Research, Society and Development, 2025)
Alcoholism is a serious public health problem that directly affects the performance and quality of life of military police officers. This study focused on analyzing the impacts of excessive alcohol consumption on professional performance, with an emphasis on raising awareness and promoting mental health in the police environment. The objective of this study was to raise awareness and provide guidance on the limits of alcohol consumption and its impact on the physical and mental health of military police officers. The methodology adopted was descriptive and qualitative, involving an educational lecture and a theatrical activity that playfully portrayed the effects of alcoholism on the daily life of the corporation. The results indicated greater engagement among police officers, critical reflection, and a change in perception regarding the topic. It is concluded that participatory educational activities strengthen prevention, well-being, and the construction of an institutional culture focused on health promotion and social responsibility.